Design and simulation of a tunable frequency OTA -C Chebyshev filter - JIANG Jin-guang; WANG Yao-nan (Tongxin xuebao)
A new transconductor operational amplifier（OTA） using active resistor of source degeneration was presented.The method was developed through acting differential pair degenerated by two MOSFET operating in the triode region as active resistor in its input stage,the circuit was designed in working in stable quiescent operating point with folded cas-cade output stage using voltage common-mode feedback（CMFB） circuit.As an tunable cutoff frequency fourth order Chebyshev lowpass filter,an accurately tunable Gm of OTA was used,which employed switching capacitor technique to tune Gm value.Simulated results show that the practical frequency response of the filter is very near to that of idealized prototype by applying 2-poly 4-metal 3.3V power supply 0.35μm CMOS technology spice model.